Acompanhamento clínico, histopatológico e avaliação dos níveis de interleucina 10 de cães com demodicose crônica - Felix, Anelize de Oliveira Campello (2010)
Demodicosis is considered one of the most severe canine skin disease. It is caused by the excessive proliferation of the Demodex canis mite, normal member of the canine skin. Skin lesions caused by the parasite predispose the skin to secondary infections that will further aggravate the patients clinical aspects. The objective of this work was to evaluate the clinical a histopathological evolution of the disease, as well as to study the seric levels of interleukin 10 (IL10) in demodicosis patients. The first study was conducted using 20 animals, 10 demodicosis patients (GD), and 10 control dogs (GC). All these animals were clinically evaluated, and submitted to deep skin scraping in search of Demodex mites. The dogs in the GD group were treated with moxidectin and evaluated in days 0, 20, 40, 60, and 80. Five of these animals were healed and submitted to skin biopsies on days 0 and 80, for the observation of histopathological alterations. A second study used 26 animals, 17 on G1 (demodicosis patients) and 9 on G2 (healthy dogs). All G1 animals were positive for demodicosis on the skin scrape test, and were submitted to clinical evaluation. Blood was harvested from all the animals, with the interleukin 10 dosage being carried out with the comrcial kit Quantikine Canine IL-10 Immunoassay® (R&D Systems) . Results obtained in the first experiment showed considerable clinical and scrape test improvement in GD, but no evolution in the histopathological patern. The GC presented higid skin and negative skin scrape test. In the second experiment, dogs in the G1 group presented hi clinical scores, indicating severe desiase. G1 had a mean IL10 level of 184,38 (+258,9) pg/mL, while the mean for G2 was11,94 (+ 2,27) pg/mL, indicating that hi levels of IL10 may be related to the development of the disease. The results described in this work show that, even when clinically healed, and with negative skin scrape test, demodicosis carriers present persistence of the lesions and the mite in the histological structure of the skin. This work also shows that demodicosis patients tend to have higher IL10 levels than healthy animals.